Optimization of Antibacterial Compounds with Ultrasonic/Microwave Assisted Extraction from Alpinae Oxyphyllae Fructus and its Antibacterial Activities - Wang, D.; Chen, W.X. (Asian Journal of Chemistry, 2014)
The work was to optimize to enhance the antibacterial activities of ethanol extracts from alpinae oxyphyllae fructus with ultrasonic-microwave assisted extraction method. And the optimum conditions were as follows: ethanol concentrations 73 %, extract temperature 54 °C, liquid-material ratio 15 and extract time 46 min. Under these conditions, the significant antibacterial activities expressed as the diameter of inhibition zones could reach 10.43 ± 1.29 mm, which was higher than traditional hot water extraction methods. On the basis of it, the minimum inhibitory concentration of extract against E coli and S. aureus, respectively was 3.00 and 1.50 mg/mL. Moreover, the content of total polyphenols and flavonoids were obtained, whose content were 7.34 ± 0.19 % and 5.95 ± 0.32 % respectively. On further study, the results showed the content of total polyphenols and flavonoids was highly correlated with the antibacterial activities with each p < 0.01(p = 0.007 and p = 0.006).